A CONCEPTUAL REVIEW OF THE FACTORS THAT INFLUENCE AUDIT DELAY - Al Hawari, Rifqy Habibi; Aprillia, Pita; Ramadhan, Argianov; Rosmanidar, Elyanti; Putri, Nurrahma Sari; Siregar, Fitri Ana (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Financial reporting is one of the important variables for a company in evaluating the company. To ensure that the financial report is in accordance with regulations or not, an audit of the financial report is required. In the auditing process, delays can occur which are influenced by several factors. This is what will be discussed in this article. The aim of this research is to find out what differences and changes have occurred in the audit delay process in the 12 year period 2010-2022. The research method used was the literature review method, research was carried out by reviewing 52 articles that had been published on Google Scholar. This research analyzes the factors that influence audit delay from an internal and external perspective. The internal factors are company size factors, profitability factors, solvency factors, company age factors, company complexity factors, and company type factors. Then the external factors are the KAP size factor, auditor specialization factor, KAP/auditor reputation factor, auditor opinion factor, auditor committee factor, auditor change factor and audit tenure factor.